Predisposition to organ-specific autoimmunity in Obese strain (OS) chickens: reactivity to thyroid, gastric, adrenal and pancreatic cytoplasmic antigens. - Khoury, E L (1982)
In addition to thyroglobulin autoantibodies, some Obese strain (OS) chickens gave organ-specific reactions with the cytoplasm of thyroid acinar cells when the sera were tested by immunofluorescence. The staining pattern was similar to that seen with human antibodies to thyroid microsomes. A proportion stained the proventricular glands of the chicken stomach in a manner indistinguishable from that of pernicious anaemia sera containing parietal cell antibodies. Isolated examples of organ-specific reactions with adrenal and exocrine pancreas were also recorded. These findings strengthen the notion that the OS chicken represents an authentic model for human organ-specific autoimmune disease. The high incidence of non-organ specific reactions complicates but does not necessarily invalidate this view since normal chickens show a propensity to develop such antibodies. However the OS chicken appears to differ from the human in being hyper-responsive to antigens in general.